Study on ecological cost-effectiveness for the thermal insulation of building external vertical walls in Poland. (1st October 2016) - Dylewski, Robert; Adamczyk, Janusz
Abstract: Improving the energy efficiency of buildings is not a new issue. It is a challenge not only in Poland but also in many other European countries, which is proved by the actions and initiatives taken by the European Union. Due to the fact that Poland lies in a warm moderate temperate zone, with transition to the impact of marine and continental climate, the issue of thermal insulation of buildings is important in terms of economy and ecology. The paper proposes a method and an analysis of the ecological cost-effectiveness for the investment involving the thermal insulation of external vertical walls for two different buildings in five climate zones located in Poland. The authors based their study on the life cycle assessment (LCA) technique. The analysis took into account different components, such as: heat sources, thermal insulation and construction materials, and usable areas of the analyzed buildings. Popular building materials on the Polish market, and more, were also included. The studies were performed on two single-family houses with a similar usable area, which are representative on the European market. The most favourable values of ecological cost-effectiveness were obtained among the examined options for most ecological thermal insulation material (eco-fibre), the type of heating with the highest environmental impact (electricity) and the most extreme (cold) climate occurring in Poland. The ecological payback period of thermal insulation investment for the studied variants were obtained in the range 0–6 years. The proposed method proved to be very helpful in assessing various options for thermal insulation investments. It can also be used in other places in the world. It allows to take into account both the environmental and economic aspects of the investment. This method could be useful for designers and energy/environmental auditors. Highlights: The environmental benefits of thermal insulation investment have been determined. The method of determining the ecological cost-effectiveness has been proposed. LCA technique has been used to determine the environmental load. Ecological cost-effectiveness for different variants of the investment has been examined. Ecological payback periods between 0 and 6 years have been obtained.